Fungal Keratitis: Epidemiology, Rapid Detection, and Antifungal Susceptibilities of Fusarium and Aspergillus Isolates from Corneal Scrapings. (20th January 2019) - Manikandan, Palanisamy; Abdel-hadi, Ahmed; Randhir Babu Singh, Yendrembam; Revathi, Rajaraman; Anita, Raghavan; Banawas, Saeed; Bin Dukhyil, Abdul Aziz; Alshehri, Bader; Shobana, Coimbatore Subramanian; Panneer Selvam, Kanesan; Narendran, Venkatapathy
Abstract : Fungal aetiology of keratitis/corneal ulcer is considered to be one of the leading causes of ocular morbidity, particularly in developing countries including India. More importantly, Fusarium and Aspergillus are reported commonly implicating corneal ulcer and against this background the present work was undertaken so as to understand the current epidemiological trend of the two fungal keratitis. During the project period, a total of 500 corneal scrapings were collected from suspected mycotic keratitis patients, of which 411 (82.2%) were culture positive for bacteria, fungi, and parasites. Among fungal aetiologies, Fusarium (216, 52.5% of 411) and Aspergillus (68, 16.5% of 411) were predominantly determined. While the study revealed a male preponderance with both the fungal keratitis, it further brought out that polyene compounds (natamycin and amphotericin B) and azoles were active, respectively, against Fusarium spp. and Aspergillus spp. Additionally, 94.1% of culture proven Fusarium keratitis and, respectively, 100% and 63.6% of A. flavus and A. fumigatus were confirmed by multiplex PCR. The sensitivity of the PCR employed in the present study was noted to be 10 fg/ μ l, 1 pg/ μ l, and 300 pg/ μ l of DNA, respectively, for Fusarium, A. flavus, and A. fumigatus. Alarming fact was that Fusarium and Aspergillus regionally remained to be the common cause of mycotic keratitis and the Fusarium isolates had a higher antifungal resistance than Aspergillus strains against most of the test drugs.